Bersinar di Pergantian Abad: Menguatnya Otoritas Kiai di Sumenep Akhir Abad XIX Hingga Awal Abad XX: Menguatnya Otoritas Kiai di Sumenep Akhir Abad XIX Hingga Awal Abad XX - lihifdzi Ayatillah, irfah (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2022)
This research discusses about one part of the social changes that occurred in Sumenep during the colonial period, namely the strengthening of local ulama in the community including the factors that caused it. This research use a historical method with a socio-political approach, this study makes use of colonial archives and other supporting literatures to explain the historical process of the rise of kiai prestige among the community and to analyze various causes and effects. The results of this study are that the strengthening of the authority of the kiai among the people of Sumenep is influenced by two factors, they are; (1) the ecological conditions of the villages in Madura which caused Islam to become a binding symbol, and (2) the change of bureaucracy from traditional to colonial with the place in the region at the same time. Meanwhile, the impact of the strengthening of the kiai's authority is marked by two things. First, the spread and development of Islamic Boarding School to remote villages in Sumenep, and the second, the high enthusiasm of the community towards Islamic-inspired movement organizations in the early twentieth century which continued even into the independence era.